Resolution of spatial and temporal heterogeneity in bevacizumab-treated breast tumors by eigenspectra multispectral optoacoustic tomography - Liapis, Evangelos; Klemm, Uwe; Karlas, Angelos; Reber, Josefine; Ntziachristos, Vasilis (Cancer Research, 2020)
Understanding temporal and spatial hemodynamic heterogeneity as a function of tumor growth or therapy affects the development of novel therapeutic strategies. In this study, we employed eigenspectra multispectral optoacoustic tomography (eMSOT) as a nextgeneration optoacousticmethod to impart high accuracy in resolving tumor hemodynamics during bevacizumab therapy in two types of breast cancer xenografts (KPL-4 and MDA-MB-468). Patterns of tumor total hemoglobin concentration (THb) and oxygen saturation (sO2) were imaged in control and bevacizumab-treated tumors over the course of 58 days (KPL-4) and 16 days (MDA-MB-468), and the evolution of functional vasculature "normalization"was resolved macroscopically. Aninitial sharp drop in tumor sO2 andTHb content shortly after the initiation of bevacizumab treatment was followed by a recovery in oxygenation levels. Rim-core subregion analysis revealed steep spatial oxygenation gradients in growing tumors that were reduced after bevacizumab treatment. Critically, eMSOT imaging findings were validated directly by histopathologic assessment of hypoxia (pimonidazole) and vascularity (CD31). These data demonstrate how eMSOT brings new abilities for accurate observation of entire tumor responses to challenges at spatial and temporal dimensions not available by other techniques today.
CRIS-Team Scopus Importer:2023-03-08